The financial analysis of the published accounts of industrial companies - Rea, Desmond (Statistical and Social Inquiry Society of Ireland, 1970)
Recently I attempted to carry out a comparative financial analysis of twenty-six indigenous Northern Ireland public companies. All twenty-six companies were quoted on the Belfast Stock Exchange and their selection was largely self-determined The analysis was based on an examination of the certified and published financial statements of the twenty-six companies for the period 1962 through 1967.
Read before the Society, 9 February 1970
Keywords: Financial accounts; Ratio analysis; Funds analysis; Northern Ireland public companies; 314.15